2023
DOI: 10.1038/s41598-023-30147-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in skin test reactions to official and defined antigens in guinea pigs exposed to non-tuberculous and tuberculous bacteria

Abstract: The single and comparative intradermal tuberculin tests (SITT and CITT) are official in vivo tests for bovine tuberculosis (TB) diagnosis using bovine and avian purified protein derivatives (PPD-B and PPD-A). Infection with bacteria other than Mycobacterium tuberculosis complex (MTC) can result in nonspecific reactions to these tests. We evaluated the performance of the skin test with PPDs and new defined antigens in the guinea pig model. A standard dose (SD) of Rhodococcus equi, Nocardia sp., M. nonchromogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This was likely why there was a high percentage (43%; 53/123) of positive cultures that contained matching mycobacterial species in both the culture isolate and DNA extracted directly from swabs. The observed diversity of NTMs identified suggests that these goats were exposed to environmental mycobacteria, many of which have been recently proven to confound M. bovis diagnosis in guinea pigs, especially when using tests based on host immune responses ( Fernández-Veiga et al, 2023 ). Further studies are needed to investigate the association between presence of NTMs and potential cross-reactivity in M. bovis specific cell-mediated immunological tests in goats.…”
Section: Discussionmentioning
confidence: 99%
“…This was likely why there was a high percentage (43%; 53/123) of positive cultures that contained matching mycobacterial species in both the culture isolate and DNA extracted directly from swabs. The observed diversity of NTMs identified suggests that these goats were exposed to environmental mycobacteria, many of which have been recently proven to confound M. bovis diagnosis in guinea pigs, especially when using tests based on host immune responses ( Fernández-Veiga et al, 2023 ). Further studies are needed to investigate the association between presence of NTMs and potential cross-reactivity in M. bovis specific cell-mediated immunological tests in goats.…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis and M. avium subsp. hominissuis , within others, could make animals react to the SITT ( 44 ). In Argentina, a study conducted by Oriani et al ( 12 ), in which cattle were inoculated with NTM isolated from soils and wetlands, this NTM included M. kansasii, M. nonchromogenicum, M. gordonae, M. arupense, M. phlei, M. fortuitum and M. peregrinum , and showed that they may cause unspecific reactions, but that these reactions are not maintained over time ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…TST relies on in vivo delayed-type hypersensitivity test that reveals infections 3 to 8 weeks after contact with M. bovis , so it is not possible to distinguish between active and latent infections. Moreover, TST has low specificity because of cross-reactive responses due to the sharing of many antigens between tuberculous and nontuberculous mycobacteria [32] . On the other hand, even though M. bovis culture is considered the gold standard for BTB diagnosis, it is time-consuming and requires specialized equipment and trained staff.…”
Section: Methodsmentioning
confidence: 99%